CeO2‐Supported Pt−Au Nanoparticles as Efficient Catalyst for CO Oxidation. Issue 2 (16th December 2022) - Wang, Haiyang; Gao, Jianjing; Zhang, Ruiyin; Ma, Hao; Ma, Cheng; Yao, Ruijuan; Liang, Miaomiao; Zhao, Yuzhen; Miao, Zongcheng
Abstract: The nanorod shaped (Pt−Au)/CeO2 catalysts with varied Pt/Au ratio were achieved from Al91.7 Ce8 AuX Pt0.15−X (X=0.05, 0.075, 0.1) precursor alloys through combined dealloying and calcination treatment. The surface morphology, microstructure as well as physicochemical features were characterized through XRD, SEM, TEM, XPS, Raman spectroscopy and N2 adsorption‐desorption tests. The catalytic measurement results imply that the (Pt0.075 −Au0.075 )/CeO2 catalyst displays optimal catalytic property with 50% and 99% reaction temperature as low as 37 °C, 80 °C, respectively. The (Pt0.075 −Au0.075 )/CeO2 was also stable after 60 h successive catalytic oxidation reaction. The outstanding catalytic performance is ascribed to the joint introduction of Pt and Au, which can suppress the agglomeration and growth of noble metal active phases during the catalytic process. What's more, the nanoscale interface formed between Pt&Au nanoparticles and CeO2 nanorods can also promote electron transfer rate, thus catalytic reaction efficiency is enhanced. The results will be of importance for design of novel nanoporous noble metal‐oxide‐based catalysts and application in exhaust treatment of fuel vehicles. Abstract : A nanorod‐structured (Pt−Au)/CeO2 catalyst was obtained from Al−Ce−Au μPt alloys through a facile two‐step dealloying and calcination treatment. The jointed introduction of Pt and Au can inhibit the agglomeration and growth of noble metal active phases, while the interface between Pt and Au and CeO2 can promote electron transfer rate and thus the overall catalytic reaction efficiency is enhanced.